Enhanced liquid tar production as fuels/chemicals from Powder River Basin coal through CaO catalyzed stepwise degradation in eco-friendly supercritical CO2/ethanol. (15th January 2020) - Liu, Fang-Jing; Gasem, Khaled A.M.; Tang, Mingchen; Xu, Bang; Huang, Zaixing; Zhang, Riguang; Fan, Maohong
Abstract: Developing eco-friendly thermal conversion technologies of coals into fuels/chemicals with minimal environmental impact is highly attractive and significant for efficient coal utilization. CaO catalyzed stepwise degradation at 350–400 °C in eco-friendly supercritical CO2 /ethanol (scCO2 /ethanol) was carried out to produce high-yield liquid tars as fuels/chemicals from Powder River Basin (PRB) coal. The total yield of the liquid tars increased from 53.9 wt% for non-catalytic stepwise degradation to 60.1 wt% for CaO catalyzed stepwise degradation, with an increase of 6.2 wt%. The resulting ash-free liquid tars are promising raw materials as clean liquid fuels for energy production due to their high H/C ratio (1.16–1.88) and heating values (32.84–35.84 MJ/kg). Compared with non-catalytic stepwise degradation, the energy recovery increases from 62.8% to 71.6% by CaO catalyzed stepwise degradation. More than 75% of the components in the liquid tars were volatilized and/or degraded at temperature <500 °C according to thermogravimetric analysis. The distributions of the functional groups and group components in the liquid tars are similar to each other. Phenols are the most abundant volatile group component in the liquid tars, accounting for about 43% of the volatile components released at 350 °C and 375 °C by CaO catalyzed stepwise degradation. The CaO promoted forming active H + and CH3 CH2 O − from ethanol, which readily attacked and cleaved weak -C-O- bonds in the PRB coal, leading to producing more phenols and arenes. Thermal dissociation of the non-covalent interactions especially hydrogen bonds or the cleavage of weak -C-O- in PRB coal could interpret the generation of phenols. Graphical abstract: Image 1 Highlights: The total yield of liquid tars is 60.1 wt% from CaO catalyzed stepwise degradation. Liquid tars have high heating values and energy recovery value reaches up to 71.6%. Liquid tars are promising feedstock for producing clean liquid fuels and chemicals. CaO facilitated producing phenols which are the dominant components in liquid tars. Mechanisms for dissociating the volatile compounds by degradation were discussed.